Highly luminescent biocompatible CsPbBr3@SiO2 core–shell nanoprobes for bioimaging and drug delivery. Issue 45 (20th October 2020) - Kumar, Pawan; Patel, Madhumita; Park, Chanho; Han, Hyowon; Jeong, Beomjin; Kang, Hansol; Patel, Rajkumar; Koh, Won-Gun; Park, Cheolmin
Abstract : A facile approach for the highly luminescent and biocompatible CsPbBr3 @SiO2 core–shell PNCs was developed. The dual biological roles of these PNCs are demonstrated, offering new directions to the stable PNCs for a variety of biomedical applications. Abstract : The encapsulation of lead halide perovskite nanocrystals (PNCs) with an inert protective layer against moisture and the environment is a promising approach to overcome hinderances for their practical use in optoelectronic and biomedical applications. Herein, a facile method for synthesizing highly luminescent and biocompatible CsPbBr3 @SiO2 core–shell PNCs with a controlled SiO2 thickness, which are suitable for both cell imaging and drug delivery, is reported. The synthesized CsPbBr3 @SiO2 core–shell PNCs exhibit bright green emission at 518 nm upon excitation of 374 nm. Interestingly, a significant increase in the photoluminescence intensity is observed with an increase in the SiO2 shell thickness, which varies with the increasing reaction time. Cytotoxicity results indicate that the CsPbBr3 @SiO2 core–shell PNCs are nontoxic, making them suitable for in vitro cell imaging using HeLa cells. Furthermore, doxorubicin physically adsorbed on the surface of CsPbBr3 @SiO2 core–shell PNCs is efficiently released in cells when the drug-loaded perovskite nanoprobes are injected in the cells, indicating that these core–shell nanoparticles can be used for drug loading and delivery. The results of this study suggest that the CsPbBr3 @SiO2 core–shell PNCs can pave the way for new biomedical applications and processes.